TRIM31 inhibits NLRP3 inflammasome and pyroptosis of retinal pigment epithelial cells through ubiquitination of NLRP3. (5th August 2020) - Huang, Peirong; Liu, Wenjia; Chen, Jieqiong; Hu, Yifan; Wang, Yuwei; Sun, Junran; Feng, Jingyang
Abstract: NOD‐like receptor protein 3 (NLRP3) is associated with age‐related macular degeneration (AMD). Retinal pigment epithelial (RPE) cells serve as the immune defense of macula, and their dysfunction causes clinically relevant changes in AMD. In the present study, oxidized low‐density lipoprotein (ox‐LDL) activated the NLRP3 inflammasome in human RPE cell line ARPE‐19. Our data showed that the expression of NLRP3, interleukin‐1β (IL‐1β), and caspase‐1 and the release of IL‐1β in ARPE‐19 cells were substantially increased by ox‐LDL, whereas the addition of NLRP3 inhibitor INF39 dose‐dependently reversed the effect of ox‐LDL. Overexpression of tripartite motif‐containing protein 31 (TRIM31) also suppressed the effect of ox‐LDL in ARPE‐19 cells. TRIM31 knockdown had similar effects with ox‐LDL but INF39 could block the effect of TRIM31 knockdown. Moreover, TRIM31 could interact with NLRP3 in ARPE‐19 cells. Overexpression of TRIM31 increased NLRP3 ubiquitination. In conclusion, the results propose that TRIM31 could enhance NLRP3 ubiquitination, therefore inhibiting NLRP3 inflammasome and pyroptosis in human RPE cells.